2021
DOI: 10.1038/s41366-021-00898-z
|View full text |Cite
|
Sign up to set email alerts
|

Life course socioeconomic position and body composition in adulthood: a systematic review and narrative synthesis

Abstract: Introduction Multiple systematic reviews have investigated the relation between socioeconomic position (SEP) and body mass index (BMI) throughout the life course. However, BMI does not capture quantity and distribution of fat and muscle, which are better indicators of obesity than BMI, and have been independently linked to adverse health outcomes. Less is known about the relation between SEP and body composition, and the literature has not been reviewed. We therefore systematically reviewed the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…We found a negative correlation between education and obesity/being overweight. The inverse relationship between education level and risk of obesity has been extensively documented in developed countries (Bridger Staatz et al. , 2021; Li et al.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a negative correlation between education and obesity/being overweight. The inverse relationship between education level and risk of obesity has been extensively documented in developed countries (Bridger Staatz et al. , 2021; Li et al.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…We found a negative correlation between education and obesity/being overweight. The inverse relationship between education level and risk of obesity has been extensively documented in developed countries (Bridger Staatz et al, 2021;Li et al, 2021a;Witkam et al, 2021;Faka et al, 2019;Oshan et al, 2020;Hern andez-Yumar et al, 2019;Choi and Cawley, 2018;Samouda et al, 2018;Newton et al, 2017;Cohen et al, 2013;Devaux et al, 2011). As the meta-analysis conducted by Cohen et al (2013) revealed the relationship between education and obesity is consistent and robust even when different measures of obesity or education are used.…”
Section: Obesitymentioning
confidence: 94%
“…Although empirical data are limited from LMICs, it appears that the development of body fat is differently influenced by societal factors in high-income countries vs. middle income countries [20]. For example, a prior study reported a negative association between socioeconomic status and fat mass in high-income countries, but a positive or no association in middle-income countries [20].…”
Section: Discussionmentioning
confidence: 98%
“…Although obesity is a health risk shared by low-, middle-, and high-income countries [18], studies in low-and middle-income countries (LMIC) are particularly limited [19]. The data that are available suggest that the influences of societal factors on PA and adiposity are different in LMIC compared to high income countries [20]. The aim of this study was to compare changes in body fat mass according to whether meeting the youth and adult PAGs from late adolescence to early adulthood (age 18 to 22 years) in a large sample of the Brazilian population.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions contribute to the differences in weight gain between low SES groups and wealthy individuals in developing countries. Studies have showed that socioeconomic status in early life and perhaps even in earlier generations have significant influence on adult obesity development (23)(24)(25). However, this relationship still varies across countries with different levels of development.…”
Section: Discussionmentioning
confidence: 99%